Contribution of Surface Distributions to Constant-Phase-Element (CPE) Behavior: 2. Capacitance. (10th January 2016) - Alexander, Christopher L.; Tribollet, Bernard; Orazem, Mark E.
Abstract : Highlights: Finite-element simulations of the impedance of electrodes with distributed capacitance. Characteristic dimension for distributed capacitance identified Characteristic frequencies found at which distributed capacitance causes time-constant dispersion Conclusion: Distributed capacitance cannot explain CPE behavior due to surface distributions Abstract: Finite–element simulations were performed to determine the influence of a radial distribution of capacitance on the impedance of ideally polarized disk electrodes. The characteristic length associated with this form of distribution was found to be the period of the distribution. This work showed that while a capacitance distribution causes frequency dispersion, this effect is seen only at frequencies that are much higher than those associated with the disk-geometry-induced frequency dispersion. Thus, a constant-phase-element associated with a surface distribution of time constants cannot be attributed to a distribution of capacitance.